Answer:
7
Step-by-step explanation:
2n - 6 = 8. Simplified version is n = 7
Answer: £18
Step-by-step explanation:
let Bridget get £x,
Stephen gets 3x, Richard gets 2(3x)
Equation is x + 3x + 6x = 60
10x = 60: x = 60/40 = 6
Bridget gets £6
Stephen gets 3x = 3 x 6 = £18
Richard gets 2(3x) = 2 x 18 = £36
3x-1-(3x-3)
3x-1-3x+3
3-1
=2
Answer:
X = -11
Step-by-step explanation:
-2 (x+3) +5x = -39
3x -6= -39
3x = -33
3x/3 = -33/3
X = -11
Answer:
54 = 2 x 27
the cube root of 27 is 3.
the answer is C
Step-by-step explanation: